Incidence, risk factors and medical cost of peripheral intravenous catheter-related complications in hospitalised adult patients. Issue 1 (January 2022) - Liu, Congcong; Chen, Lin; Kong, Dong; Lyu, Fangfang; Luan, Linlin; Yang, Lijuan
Background: Peripheral intravenous catheters (PVCs) are widely used vascular access devices for infusion therapy; however, they are associated with relatively high failure rates. This study aimed to identify the incidence, risk factors and medical costs of PVC-induced complications in adult hospitalised adult patients in China. Methods: An observational, prospective study on 1069 patients lasting 5 months was conducted at a tertiary teaching hospital. Results: Infiltration ranked first among PVC complications with an incidence of 17.8%, followed by occlusion (10.8%) and phlebitis (10.5%). Most complications in phlebitis (88.4%) and infiltration (93.7%) were Grade 1. Catheters left in for over 96 h did not show a higher incidence of complications. Patients from the surgical department were more susceptible to infiltration, phlebitis and occlusion. The 26 gauge (Ga) catheters decreased the risk of phlebitis and occlusion, whereas 24Ga catheters increased infiltration rates. Infusing irritant drugs increased phlebitis and infiltration rates. The presence of comorbidities and non-use of needleless connectors were associated with occlusion. Compared with forearm insertion, the risk of occlusion nearly doubled with the dorsum of the hand insertion and the risk of infiltration tripled with antecubital fossa insertion. Medical treatment costs for PVC complications ranged from 0.3 to 140.0 CNY. Conclusions: Infiltration is the most common PVC-related adverse event. Clinically-indicated instead of routine replacement of catheters is safe. More efforts are warranted to improve nurses' adherence to recent guidelines in terms of insertion site selection and needleless connector utilisation to reduce medical costs associated with catheter replacement.